Observations on disinflation in transition economies - Paul Wachtel; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
The transition economies were remarkably successful in curbing the inflation that took place after the initial transition and shocks and, more recently, most of the countries have brought inflation down to the levels found in major developed countries.In this paper we review the experiences and show how fiscal discipline, monetary policy and exchange rate policy contributed to the outcome.In addition, we note that the influence of EU accession on institutions and policy may have played an important role.The paper also surveys the literature on the quality of the inflation data, the extent to which necessary relative price adjustments have occurred and the size of the Balassa-Samuelson effect.Case studies of disinflation in four countries are presented: Poland, Romania, Estonia and Russia.
URN:NBN:fi:bof-201408072138
Keywords: 330